Evaluation study on the implementation of the Early Literacy Through English (ELiTE) pilot programme - Mansor, Azlin Norhaini; Darus, Zabani; Ibrahim, Mohd Burhan; Sarif, Sharida Hanim (2009)
The study was carried out to evaluate the implementation of the Early Literacy Through English (ELiTE) pilot programme, which aimed at increasing Year One pupils’ literacy in English. It was an intervention programme designed by the Ministry of Education (MoE) to get the pupils ready to learn Science and Mathematics in English. The study focused on the three aspects of the implementation process, namely the effectiveness of the ELiTE Module, the level of teacher readiness in implementing the programme and the effect of the programme on pupils’ achievement in the English Language. A total of 244 teachers teaching Year One students, from 57 primary schools were selected to carry out the ELiTE programme. The number of pupils involved were 767 Year One pupils from the ELiTE Programme pilot schools and 767 Year One pupils from schools that were not invoved in the ELiTE programme. Examination papers, questionnaires and structured interview protocols were used as research instruments. The findings indicated that the content of the ELiTE Module was moderately comprehensive and that the module had achieved 15 of the 18 ELiTE objectives listed. The study also showed that, teachers’ level of readiness to implement the programme was moderate. The overall effect of the ELiTE programme which was based on pupils’ examination results, showed that the pupils involved in the ELiTE pilot programme scored significantly higher than pupils who were not involved with the programme. Finally, the majority of teachers agreed that the programme should be expanded to all primary schools, especially those with moderate and low academic achievement.